REMEDIES AVAILABLE TO A SELLER IN THE CASE OF A BUYER’S BREACH OF CONTRACT ON INTERNATIONAL SALE OF GOODS - Zdravkovic, Uros (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The remedies available to a seller in the case of a buyer’s breach of contract on international sale of goods are predominantly contained in articles 61-65 of the CISG. At the first place, the article 62 of the CISG entitles the seller to require the buyer to perform its obligations. In accordance with article 63 of the CISG, the seller may fix an additional period of time of reasonable length for performance by the buyer of his obligations. Article 64 defines the conditions under which the seller is entitled to declare the contract avoided. The first situation in which the seller can avoid the contract is where the buyer has committed a fundamental breach of contract. Article 64 also provides that the seller can avoid the contract if the buyer has not paid the price or taken delivery of the goods within the additional period of time fixed by the seller under article 63(1). Where the buyer has paid the price, the seller loses the right to avoid the contract if it does not declare avoidance within the periods stated in article 64(2). In cases of late performance, the seller loses the right to declare the contract avoided unless it does so before becoming aware that performance has been rendered. In regard to any breach other than late performance, there is a distinction according to whether or not the seller has fixed an additional period for performance in accordance with article 63 (1). In the absence of an additional period for performance, the seller loses the right to declare the contract avoided unless it declares avoidance within a reasonable time after the seller knew or ought to have known of the breach. Where the seller has fixed an additional period of time for performance by the buyer, the seller loses the right to declare the contract avoided unless it declares avoidance within a reasonable time after the expiration of the additional period fixed by the seller or after the buyer has declared that it will not perform its obligations within such additional period. Finally, if the buyer fails to make specification of the goods either on the date agreed upon or within a reasonable time after receipt of a request from the seller, the seller may, without prejudice to any other rights he may have, make the specification himself in accordance with the requirements of the buyer that may be known to him.